SISTEM DAN PROSEDUR PELAYANAN IZIN USAHA INDUSTRI PETERNAKAN DI KABUPATEN BANJARNEGARA - Nico Setiadi; Indriati Amarini (Wijayakusuma Law Review, 2023)
The Banjarnegara Regency One Stop Integrated Licensing and Investment Service (DPMPPTSP) is one of the units in the region that organizes Online Single Submission. However, the implementation has not been maximized, so I want to know what obstacles occur in the industrial business permit process in Banjarnegara district. The purpose of this study was to identify and analyze the efforts of the One-Stop Integrated Investment and Licensing Service in implementing the granting of electrical industrial business permits. And knowing the obstacles that occur in the process of implementing industrial business permits in Banjarnegara Regency. The method in this research is using the normative juridical method. The data in this study were obtained through library research, namely a series of reading, recording, and citing books as well as using secondary data or information and explanations through data requests from relevant agencies based on the objectives. study. The results of this study indicate that the livestock industry business licensing process online through the Online Single Submission there are obstacles faced by the Office of Investment and One Stop Integrated Services such as incomplete data provided by the applicant in the industrial business permit process, besides that there are also obstacles to the community such as the type of business fields in the Online Single Submission that are not yet complete. Keywords: Licensing, Business, Industry. Dinas Penanaman Modal dan Pelayanan Perizinan Terpadu Satu Pintu (DPMPPTSP) Kabupaten Banjarnegara termasuk salah satu dari unit di daerah yang menyelenggarakan Online Single Submission. Namun dalam pelaksanaannya belum maksimal, sehingga penulis ingin mengetahui kendala apa saja yang terjadi dalam proses izin usaha industri di kabupaten Banjarnegara. Tujuan penelitian ini adalah untuk mengetahui dan menganalisa upaya Dinas Penanaman Modal dan Pelayanan Perizinan Terpadu Satu Pintu dalam melaksanakan pemberian izin usaha industri secara elektrik. Dan mengetahui hambatan yang terjadi dalam proses pelaksanaan izin usaha industri di Kabupaten Banjarnegara. Metode dalam penelitian ini adalah menggunakan metode yuridis normatif, Data dalam penelitian ini diperoleh melalui Penelitian Kepustakaan yaitu serangkaian kegiatan membaca, mencatat, dan mengutip buku-buku serta menggunakan data sekunder atau informasi dan keterangan-keterangan melalui permintaan data pada instansi terkait yang berlandaskan pada tujuan penelitian. Hasil penelitian ini menunjukkan bahwa proses perizinan usaha industri peternakan secara online melalui Online Single Submission terdapat hambatan yang dihadapi Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu seperti kurang lengkapnya data yang diberikan pemohon dalam proses izin usaha industri, selain itu terdapat juga hambatan pada masyarakat seperti jenis bidang usaha didalam Online Single Submission yang belum lengkap. Kata Kunci : Perizinan, Usaha, Industri.